Technology and performance: Carbon Nanotube (CNT) Field Effect Transistor (FET) in VLSI circuit design - .., Soheli Farhana; Noordin, Mohd Fauzan (IEEE, 2016)
Nano size carbon, such as carbon nanotubes (CNTs) and graphene has remarkable electronic properties for high-frequency electronics in terms of designing VLSI circuits. CNTFETs are the best candidates for nano electronics as well as upcoming digital devices in near future. An intensive review is presented in this paper. The structure, materials, application and the characteristics of CNTFETs are analyzed here for the future generation miniature device.